The Role of Economic Feasibility in Advancing Technology Adoption among UMKM - Hanif Rani Iswari; Siti Nur Ainun (Bulletin of Management and Business, 2023)
Technology hilirization in micro, small, and medium enterprises (UMKM) often encounters barriers not primarily rooted in technical limitations, but in economic uncertainty and decision-making constraints. Many technologies with proven technical performance fail to be adopted due to unclear value propositions, ambiguous cost structures, and limited financial comprehension among UMKM actors. This study aims to examine the role of economic feasibility as a critical bridge between technical readiness and technology adoption in resource-constrained UMKM contexts. Using a qualitative explanatory approach combined with techno-economic analysis, this study investigates how feasibility indicators such as production cost, break-even point, investment recovery, and perceived financial risk influence adoption decisions. Empirical insights are drawn from UMKM cases involved in food and agro-processing technology hilirization. The findings reveal that economic feasibility does not merely function as a financial evaluation tool, but also as a cognitive framing mechanism that shapes risk perception, confidence, and managerial commitment toward innovation adoption. Technologies accompanied by clear, transparent, and context-relevant feasibility information demonstrate significantly higher acceptance and readiness for adoption. This study contributes to the literature by positioning economic feasibility as an adoption readiness instrument rather than a post-implementation assessment. Practically, the results suggest that successful hilirization strategies for UMKM should integrate economic feasibility analysis alongside technical validation to ensure sustainable and scalable technology adoption.